2011
DOI: 10.1016/s0954-6111(11)70012-9
|View full text |Cite
|
Sign up to set email alerts
|

CD14 gene polymorphism is not associated with asthma but rather with bronchial obstruction and hyperreactivity in Slovenian children with non-atopic asthma

Abstract: Our results suggest that CD14 is associated with asthma severity in Slovenian children with non-atopic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The number of cases varied from 10 to 644, and controls from 115 to 1858 subjects. CD14 rs2569190 polymorphism, also known as C-260T or C-159T, was studied in 16 studies [10,12,13,19-21,34,36-40,42-45]. Only one study found an association of this polymorphism with childhood asthma, showing an association of the T allele with decreased asthma severity (Table 3) [19].…”
Section: Resultsmentioning
confidence: 99%
“…The number of cases varied from 10 to 644, and controls from 115 to 1858 subjects. CD14 rs2569190 polymorphism, also known as C-260T or C-159T, was studied in 16 studies [10,12,13,19-21,34,36-40,42-45]. Only one study found an association of this polymorphism with childhood asthma, showing an association of the T allele with decreased asthma severity (Table 3) [19].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 case–control studies [11,17,22,23,33,36,47] conducted among nonatopic asthma were included in this meta-analysis. Overall, the pooled results indicated that there was no significant relationship of CD14 −159C/T and nonatopic asthma risk in dominant model (TT+TC vs CC: OR = 1.05, 95% CI = 0.82–1.33, P = 0.700) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the data have yielded conflicting results. [11,21,3036] Therefore, we performed this updated meta-analysis to investigate the more precise association between the CD14 −159C/T variant and asthma risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthmatic (allergic and non-allergic) patients, children aged between 7 and 18 years with mild or moderate persistent asthma treated after 01.01.2008 in the University Medical Centre Maribor were enrolled in the study, considering inclusion and exclusion criteria (Perin et al, 2011). Asthma was diagnosed according to NAEPP (National Asthma Education and Prevention Program) and ATS (American Thoracic Society) criteria.…”
Section: Study Subjectsmentioning
confidence: 99%